Implementasi Arsitektur Hierarchical Model View Controller (HMVC) Dalam Portal Akademik - Ardi, Noper; Adri, Muhammad; Azhar, Nelda (Universitas Negeri Padang, 2021)
Rapid development in information technology directly impact on the education system in Indonesia, including on technology and vocational education. Computerized process used at every level of the education system makes information technology as an integral part of the education system in various countries, including Indonesia. SMKN 1 Padang as one of a big educational institutions and vocational technology in the city of Padang. However, the utilization of information technology in SMK 1 Padang is still very minimal. Data management process and learning activities are still carried out manually. With the large number of membership programs and number of students, this wayof process less efficient considering the chance of the possibility of error, either in the form of data inconsistencies as a result of the mistake input process value by teachers as well as the possibility of errors in data processing of other student's academic. Coupled with the length of time required to process the data and the number of resources required. Hence the need for a system that manages all the data management process in SMK 1 Padang. In terms of the development and management of the system, often found difficulty in developing the system further. One effort that can be done is to design and implement a system of academic portal as a means of academic activities management at SMK 1 Padang. Academic Portal was designed and developed based on architecture HMVC using the programming language PHP and MySQL database, with CodeIgniter framework, bootstrap framework, javascript, ajax, HTML5 and CSS3. Implementation of HMVC architecture in academic portal at SMK 1 Padang is one of solution to the problem of data management academic at SMK 1 Padang. The system was designed and developed the portal is expected to support process optimization performance of academic services at SMKN 1 Padang. HMVC architecture implemented in the portal system for further development of the portal system.